Answer:
A' (-4, - 7), B' (-5, -4), C' (-4, -3), D' (-3, -4)
Explanation:
Rule of rotation about the origin at an angle of 90° in the counterclockwise direction:
The stated value of (x, y) after performing the translation are switched or interchanged, with x used as the y coordinate value and the negative value of y used as the x coordinate value. That is ;
(x, y) - - - -> (-y, x)
Solving the problem above:
Applying translation: (x-2, y+3), then rotating about the origin at 90° in the counterclockwise direction.
A =(-5, 1) = (-5 - 2, 1 + 3) = (-7, 4)
(-7, 4) - - -> A' = (-4, - 7)
B =(-2, 2) = (-2 - 2, 2 + 3) =(-4, 5)
(-4, 5)- - -> B' = (-5, -4)
C =(-1, 1) = (-1 - 2, 1 + 3) = (-3, 4)
(-3, 4) - - -> C' = (-4, -3)
D =(-2, 0) = (-2 - 2, 0+3) =(-4, 3)
(-4, 3)- - -> D' = (-3, -4)